1965
DOI: 10.1111/j.1365-3180.1965.tb00350.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Selective Herbicides for Kale in the United Kingdom

Abstract: The purpose of this paper is firstly to describe the background of an investigation started in 1961 to develop new herbicides for the control of weeds in agricultural kale, Brassica oleracea vars, acephala D.C, SinA fruticosa Metz, and secondly to present the results of four experiments concerned with the effects of weeds on the yield of' kale. The results of the herbicide investigation are to be presented in subsequent papers.Kale as grown in the United Kingdom is a valuable fodder crop and relatively easy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1966
1966
1968
1968

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In the trial reported above the presence of weeds did not affect crop growth during the first month after crop emergence. It has, however, been found that weed growth early in the life of the crop can reduce the yield of kale (Elliott & Cox, 1965). Since it is not yet possible to predict for any particular situation the effects early in the life of the crop, only a selective soil-acting herbicide applied pre-emergence would provide a reliable method of eliminating the effects of weed competition in kale.…”
mentioning
confidence: 99%
“…In the trial reported above the presence of weeds did not affect crop growth during the first month after crop emergence. It has, however, been found that weed growth early in the life of the crop can reduce the yield of kale (Elliott & Cox, 1965). Since it is not yet possible to predict for any particular situation the effects early in the life of the crop, only a selective soil-acting herbicide applied pre-emergence would provide a reliable method of eliminating the effects of weed competition in kale.…”
mentioning
confidence: 99%